2018
DOI: 10.1136/jech-2018-211050
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and longitudinal change in blood pressure and mortality in a Chinese cohort

Abstract: Our findings emphasise that hypotension and stage 3 hypertension were associated with an increased risk of all-cause mortality. Longitudinal change from normotensive or prehypertensive levels to 140/90 mm Hg or higher could increase the risk of total and cardiovascular mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Tea consumption was defined as drinking at least one cup of tea per day for 1 year. Valid physical activity was defined as at least 15 min at a time [30]. Health conditions included depression symptom (yes or no) and the number of chronic conditions (none, one, two or more).…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…Tea consumption was defined as drinking at least one cup of tea per day for 1 year. Valid physical activity was defined as at least 15 min at a time [30]. Health conditions included depression symptom (yes or no) and the number of chronic conditions (none, one, two or more).…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…A study examining 4658 oldest old individuals (mean age = 92.1 years) in China observed the risk of all-cause mortality only for SBP<107 mmHg. Studies conducted among one million South Koreans aged 30–95 years (Kimm et al, 2018; Yi et al, 2016) and over 160,000 Chinese aged 40–69 years (Wang et al, 2018), reporting a J- or U-shaped relationship between BP and all-cause mortality, observed higher mortality risk only for SBP <90 mmHg. And, a previous study from Singapore, among 30,692 individuals aged 48–85 years, found an increased risk of cardiovascular mortality only for SBP <100 mmHg among those aged ≥60 years (Koh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension has been recognized as a significant risk factor for cardiovascular disease, which has become a nationwide epidemic in China [18, 19]. Some research emphasized that longitudinal change from normotensive or prehypertensive levels to 140/90 mm Hg or higher could increase the risk of total and cardiovascular mortality [20]. The prevalence of hypertension is rising fast, yet it remains inadequately controlled.…”
Section: Discussionmentioning
confidence: 99%